Differential Equations Arising from the Generating Function of the (r, β)-Bell Polynomials and Distribution of Zeros of Equations - Kyung-Won Hwang; Cheon Seoung Ryoo; Nam Soon Jung (Mathematics, 2019)
In this paper, we study differential equations arising from the generating function of the <semantics> ( r , β ) </semantics> -Bell polynomials. We give explicit identities for the <semantics> ( r , β ) </semantics> -Bell polynomials. Finally, we find the zeros of the <semantics> ( r , β ) </semantics> -Bell equations with numerical experiments.